Fabrication of Ag/ZnO@N-Carbon Core@Shell Photocatalyst for Efficient Photocatalytic Degradation of Rhodamine B - Yang, Xiaobing; Hu, Jiapeng; Pan, Junjie; Shen, Yongbin; Cheng, Kejun (Frontiers in Chemistry, 2022)
Photocatalytic degradation method has been recognized as an effective way to eliminate the contamination of environment. However, developing photocatalysts with excellent photocatalytic properties are still a big challenge. In this paper, Ag doped ZnO coating with a layer of N doped porous carbon (Ag/ZnO@N-carbon) was successfully synthesized by using polyvinyl pyrrolidone (PVP) modified ZIF-8 as precursor via adsorption, hydrothermal treatment, in situ growth and carbonization processes. The physical and chemical properties of all samples were characterized by X-ray powder diffraction (XRD), scanning electron microscope (SEM), electron transmission microscopy (TEM) and so on. The results show that Ag doping does not change the crystallinity of ZnO, but broaden its photo-response property. The coating of N doped carbon can improve the specific surface area of photocatalyst. The photocatalytic activity of all samples was evaluated by degradation of rhodamine B (RhB) solution under UV light irradiation for 25 min. Ag/ZnO@N-carbon exhibits the highest photocatalytic activity for degradation of RhB with a degradation of 98.65%. Furthermore, Ag/ZnO@N-carbon also has high stability. Based on the characterization, possible mechanism for degradation of RhB by Ag/ZnO@N-carbon under UV light irradiation was proposed.